Syria Profile of the Epidemiology and Management of Early Childhood Caries Before and During the Time of Crisis - Easter Joury (Frontiers Media S.A., 2019)
Syria has witnessed the greatest humanitarian crisis of forcibly displaced population since World War II. The present review aimed to outline Syria's profile of the epidemiology and management of early childhood caries (ECC). Before the crisis, the burden of ECC amongst Syrian pre-schoolers had been growing in prevalence and severity. Comparable data showed an increase in the burden of ECC amongst Syrian children aged five years, rising from 74% in 1991 to 81% in 2011, with a dmft value of 8.6. A similar increase was observed in the burden of ECC amongst Syrian children aged three years, rising from 50% in 1991 to 56% in 2011, with a dmft value of 6.1. Whilst there are no data on the burden of ECC during the current crisis, estimates could be extrapolated from data on the current burden of dental caries amongst Syrian primary school children living inside Syria or in informal settlements outside Syria. Such data suggested that the burden of ECC might have further increased amongst Syrian pre-schoolers during the crisis time. This is due to the crisis exacerbating effect on ECC risk factors, in terms of increasing the existing high sugar intake amongst Syrian pre-schoolers as well as increasing different barriers Syrian families face to fresh foods, sugar-free medicines, oral hygiene and fluoride products and accessing essential preventative dental care. Tackling the growing burden of ECC amongst Syrian pre-schoolers should not be postponed till post-crisis time. The seed work for relevant public health interventions could start and be embedded in different health and social initiatives taking place during the time of crisis. A number of public health interventions informed by relevant international and local (Syrian) studies conducted during the time of crisis have been suggested to tackle the burden of ECC amongst Syrian young children. They include a mix of upstream, midstream, and downstream interventions that aim to reduce sugar intake, improve feeding and oral hygiene practices, increase access to an appropriate source of fluoride and build the capacity of the Syrian dental and wider workforce to tackle the growing burden of ECC in Syrian pre-schoolers.